THE TOOL OF RESISTANCE MONITORING OF PLUTELLA XYLOSTELLA, (L.) AND ITS FIELD VALIDATION USING EMAMECTIN BENZOATE AND DIAGNOSTIC CONCENTRATION DETERMINATION - Tarwotjo, Udi; Situmorang, Jesmandt; Martono, Edhy; Rahadian, Rully (NICHE Journal of Tropical Biology, 2020)
In Indonesia, cabbage pest control is still heavily dependent on the use of insecticides. Although insecticides have many advantages, i.e., reducing the populations of pest quickly, easy to use, and economically advantageous, but it has the negative impact especially the emergence of resistant pest species.The objective of this study are: (1) to monitore the resistance of Plutella xylostella population toward insecticide residues of emamectin benzoate by diagnostic concentration determination, (2) to validate the diagnostic concentration in the field. P. xylostella population were collected from some cabbage farms in Central Java i.e., Bandungan, Sumowono, Cepogo, Kejajar, Kertek, Tawangmangu, Plalar, Puasan, Kaponan, and Keteb.Determination of LC90 was tested using probit analysis. The results showed that five of the eleven tested populations have sensitivity c2 value < c2 table, namely population Selo, Gedongsongo, Gondosuli, Kejajar, and Plalar. The determinated diagnostic concentration is LC90 = 2443.99 ppb with the lowest concentration limits 1213.67 ppb and the highest is 4921.53 ppb, because of the testing results of the sensitivity of all tested populations are still susceptible to emamectin benzoate with mortality > 90% at a concentration of 2000 ppb. The results of validation diagnostic concentration (2443.99 ppb), indicating the mortality percentage caused by eleventh population ranged from 82.76% to 95%, the value of c2 value is smaller than c2 table (df = 1; ? = 0.05) = 3.84. Therefore the diagnostic concentration (ppb 2443.99) is valid for effective monitoring tool for the development of resistance of P. xylostella population. The conventional method to monitor resistance is less sensitive to the resistance emerging occurrence. Therefore, it is necessary to develop monitoring methods which are more sensitive to small changes in the frequency of resistance, by using diagnostic concentration.